The Promise of Total Institutions in the Sociology of Organizations: Implications of Regimental and Monastic Obedience for Underlife - Mikaela Sundberg (Emerald Publishing Limited, 2024)
Goffman's (1961) work on total institutions has been relatively neglected in the fields of organizational research. This paper compares the conceptions of obedience to authority in two different types of voluntary total institutions and how such conceptions affect interaction contrary to the aims of the organizations. Consequently, by addressing how conceptions of authority and constructions of the obedient self shape conditions for underlife, the analysis provides knowledge about the variety of ways in which total institutional authority works and contributes to the understanding of the mechanisms of organizational underlife.
10.1108/S0733-558X20240000090010; 10.1108/S0733-558X20240000090010; Sociological Thinking in Contemporary Organizational Scholarship; EBP109300890